Copy number variation in the mouse genome: implications for the mouse as a model organism for human disease - Cutler, G. (S. Karger AG, 2009)
Individuals within a species have genetic differences which ultimately result in the spectrum of phenotypic variation that we observe. Genetic variation exists at the nucleotide level in the form of single nucleotide polymorphisms (SNPs), and at a structural level as inversions, deletions and amplifications of larger stretches of nucleotides. Profiling of human and mouse genomes has identified numerous genomic segmental copy number variations (CNVs) throughout these genomes. Since inbred mice are widely used laboratory models for the study of both normal and disease biology, it is crucial that we understand the full scope of genetic variation, including CNVs, within these animals. These genetic differences can inform us about the history of a population or species, enlighten us on gene function, and guide our selection of a model system for the study of human disease.